A model predictive vertical motion control of a passenger ship. (15th August 2019) - Kucukdemiral, Ibrahim Beklan; Cakici, Ferdi; Yazici, Hakan
Abstract: In this study, the design problem of a Model Predictive Controller (MPC) for attenuation of vertical motions of a passenger ship which is subject to irregular wave excitations is investigated. The proposed design considers actuator amplitude and rate saturation phenomenon. The motion control system of the ship utilises a pair of active stabilizing fins mounted to the head and tail. First, irregular long crested head waves are implemented by a well-established randomization theory in order to find heave force and pitch moment at F n = 0.40 and F n = 0.50 in the time domain. Then, a two-degree-of-freedom mathematical model, in which pitch and heave motions are coupled with the approximation of convolution integrals is solved to obtain the uncontrolled motions and accelerations of the ship. Finally, considering the physical amplitude and rate limitations of the active fin mechanism, an MPC design is proposed to obtain a practically applicable state-feedback control law for attenuating vertical motion of a passenger ship. The performance of the MPC is also compared with an elipsoid based H ∞ controller. An extensive amount of simulation studies are presented at the end to illustrate the effectiveness of the proposed approach. Highlights: Cummins' equation is used for the mathematical model in irregular waves. Approximation of the convolution integral is used for fluid memory effects. It is aimed to mitigate vertical ship motions by designing a model predictive controller (MPC). Proposed optimal MPC considers actuator magnitude and rate saturation phenomenon. Performance of the proposed MPC compared with an H∞ controller developed for systems having magnitude and rate saturation.